Roles of the Pumilio domain protein PUF3 in Trypanosoma brucei growth and differentiation - Marucha, Kevin; Clayton, Christine (Parasitology, 2020)
Trypanosomes strongly rely on post-transcriptional mechanisms to control gene expression. Several Opisthokont Pumilio domain proteins are known to suppress expression when bound to mRNAs. The Trypanosoma brucei Pumilio domain protein PUF3 is a cytosolic mRNA-binding protein that suppresses expression when tethered to a reporter mRNA. RNA-binding studies showed that PUF3 preferentially binds to mRNAs with a classical Pumilio-domain recognition motif, UGUA[U/C]AUU. RNA-interference-mediated reduction of PUF3 in bloodstream forms caused a minor growth defect, but the transcriptome was not affected. Depletion of PUF3 also slightly delayed differentiation to the procyclic form. However, both PUF3 genes could be deleted in cultured bloodstream- and procyclic-form trypanosomes. Procyclic forms without PUF3 also grew somewhat slower than wild-type, but ectopic expression of C-terminally tagged PUF3 impaired their viability. PUF3 was not required for RBP10-induced differentiation of procyclic forms to bloodstream forms. Mass spectrometry revealed no PUF3 binding partners that might explain its suppressive activity. We conclude that PUF3 may have a role in fine-tuning gene expression. Since PUF3 is conserved in all Kinetoplastids, including those that do not infect vertebrates, we suggest that it might confer advantages within the invertebrate host.
Gesehen am 14.09.2020